Increasing and sustaining productivity in subtropical and tropical plantation forests: Making a difference through research partnership - Nambiar, E.K.S.; Kallio, M.H. (Center for International Forestry Research, 2008)
This research project was initiated in 1995 to address some concerns of many people, including scientists, who were questioning the prospects of tropical plantations established in short-rotation forestry as a sustainable natural resource. It is an international partnership of public and private organisations coordinated by the Center for International Forestry Research (CIFOR). It is based on the proposition that productivity is the foundation of successful plantation forestry managed for wood production and/or ecosystem services. The main aim was to examine critically effects of site management on productivity of successive rotations of plantations and on soils. The project has 16 experimental sites (10 eucalypt, 4 acacia and 2 conifers) in Australia, Brazil, Congo, China, India, Indonesia, South Africa and Vietnam. From results gathered for a decade in plantations, with growth rates from 6 to 46 m3 ha-1 yr-1 in a range of environments and forest management conditions, we conclude that subtropical and tropical plantations can be managed to increase and sustain productivity. Conserving site resources (organic matter and nutrients) to maintain production is very important. No major risks to soils were identified that cannot be managed by scientifically-based practices. One site had a problem with a fungal pathogen and no insect problems were observed at any site. The capacity of the individuals and organisations to explore new opportunities for sustainable management has been greatly strengthened through capacity building, mutual learning and sharing of information with complete transparency. The project has made significant impacts on forest management in partner organisations and developed options for improving plantation productivity of their plantations. Impacts are extending beyond the boundaries of partners’ plantation areas. Questions of long-term sustainable production can not be resolved from experiments of one rotation at a few sites so there is a compelling case to continue and build on this research programme to support plantation forestry in the tropics.